Zasada przyczynowości a współczynnik podmiotowy w wyjaśnianiu zjawisk politycznych (Świat Idei i Polityki, 2007)
The article undertakes the analysis of problem while explaining the discrepancy among the causal principle [theoretical concept understood as hermetic relation between cause and result, according to thesis: definite cause leads always (and only) to definite result] and coefficient subject [there are different types of political subjects (individual and collective participants of political life) as well as relatively stable, gradiative property subject, that is subjectivity. Additionally, coefficient subject is designed to show the changes and processes in social structure]. In this case in the article the following issues are analysed: the problem with defining the cause which determines the coefficient subject, the problem with characterising the causes determining the coefficient subject, the problem with indetermination in political life (especially political phenomenon), that is with practical negation of the causal principle. The consequence of all these issues is the thesis that explanations of the facts and processes must not be carried out by using firm directives, but inversely - by using twoway analysis (coincidence of subjective and objective factors, in which the practical indetermination is written).